Pengaruh Kompetensi Sumber Daya Manusia, PenerapanSistem Pengendalian Intern, Penerapan StandarAkuntansi Pemerintah Dan Pemanfaatan TeknologiInformasi Terhadap Kualitas Laporan KeuanganPemerintah Daerah(Studi Empiris Pada SKPD Kabupaten Sukoharjo) - Cahyandari, Devie Amelia; , Dr.Triyono, S.E., M.Si (2017)
This research aims to know the influence of human resources competences, the application of internal control systems, the application of government accounting standards and the utilization of technological information toward the quality of the financial statement of local government in SKPD of Sukoharjo Regency. This research included the quantitative research. The sample of this research was determined by purposive sampling technique and it was obtained 94 respondents. The data analyzed by using multiple linier regression with SPSS software 17 version. The result of this research showed that the competence of human resources, the application of accounting standards and the utilization of technological information gave influence on the quality of the local Government financial statement, while the application of the internal control systems did not give affect on the quality of the local Government financial's statement.